1997
DOI: 10.1038/sj.onc.1201080
|View full text |Cite
|
Sign up to set email alerts
|

Regulated ectopic expression of cyclin D1 induces transcriptional activation of the cdk inhibitor p21 gene without altering cell cycle progression

Abstract: Cyclin D1 plays a key regulatory role during the G 1 phase of the cell cycle and its gene is ampli®ed and overexpressed in many cancers. To address the relationship between cyclin D1 and other cell cycle regulatory proteins, we established human glioma and rodent ®broblast cell lines in which cyclin D1 expression could be regulated ectopically with tetracycline. In both of these cell lines, we found that ectopic expression of cyclin D1 in asynchronously growing cells was accompanied by increased levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
71
2
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 44 publications
11
71
2
1
Order By: Relevance
“…Cells with high levels of cyclin D1 are generally thought to be more likely to undergo an apoptotic cell death in response to ionizing radiation [5,6,10]. Cyclin D1, on the other hand, binds to the CDK inhibitors p21 and p27 [14,15] and, on the other hand, induces expression of these CDK inhibitors [16][17][18]. To study these complex interactions, Schwarts et al [19] demonstrated the effect of overexpression of cyclin D1 on apoptosis induced by radiation, which involves induction of p53 and p21.…”
Section: Discussionmentioning
confidence: 99%
“…Cells with high levels of cyclin D1 are generally thought to be more likely to undergo an apoptotic cell death in response to ionizing radiation [5,6,10]. Cyclin D1, on the other hand, binds to the CDK inhibitors p21 and p27 [14,15] and, on the other hand, induces expression of these CDK inhibitors [16][17][18]. To study these complex interactions, Schwarts et al [19] demonstrated the effect of overexpression of cyclin D1 on apoptosis induced by radiation, which involves induction of p53 and p21.…”
Section: Discussionmentioning
confidence: 99%
“…Besides p53, transcription factor Ap-2 (Zeng et al, 1997), E2F-1/DP-1 complex (Hiyama et al, 1997), E2A (Prabhu et al, 1997), an ets-oncogene related E1AF (Funaoka et al, 1997), C/EBP , RAR (Liu et al, 1996a), VDR (Liu et al, 1996b), STATs (Chin et al, 1996), and Sp1 family (Biggs et al, 1996;Li et al, 1998;Owen et al, 1998;Prowse et al, 1997;Yan and Zi , 1997) are known to stimulate p21 promoter activity. Our results show that Ras induces p21 transcriptionally and that the Ras-responsive region in p21 promoter spans a short region downstream of the nucleotide 7110 relative to the transcription start site.…”
Section: Discussionmentioning
confidence: 99%
“…Since the activation of Akt promotes cell cycle progression by modulating the expression (Brennan et al, 1997;Muise-Helmericks et al, 1998) and stabilization of cyclin D1 (Graff et al, 2000) and the SPF is an indicator of the proliferative state of the cells, the negative association between pAkt and SPF was unexpected. Nevertheless, an increase in cyclin D1 does not always lead to cell cycle progression (Hiyama et al, 1997;Mitsuuchi et al, 2000), and in some cases the expression of cyclin D1 has been associated with low proliferative rate in clinical material (Nielsen et al, 1999). Furthermore, the survival analysis indicated that patients in the pAkt positive group tended to have a higher risk to develop distant recurrence compared to the negative group, and the multivariate analysis showed that pAkt was an independent prognostic factor in addition to nodal status and SPF.…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%